Behaviour of New Curved in Plan Composite Reinforced Concrete Beams - Witwit, Dolfocar Ali Usamah; Jasim, Nabeel Abdulrazzaq (Basrah Journal for Engineering Sciences, 2022)
New composite reinforced concrete beams, in which reinforced concrete component is connected to steel T-section, are proposed. The stirrups of the beam were utilized as shear connectors by passing them through drilled holes in the web of the steel T-section. Experimental test and numerical analysis were conducted to determine the behaviour of such beams when subjected to combined shear, torsion, and bending stresses. Full scale one conventional reinforced concrete curved in plan beam C1, and four composite reinforced concrete ones, C2 to C5, were tested. The degree of shear connection between the two components of beams C2 to C5 was changed by varying the number of stirrups which are used as shear connectors. The increase in load carrying capacity of the composite reinforced concrete beams reached 55 % for beam C4 as compared to that of ordinary reinforced concrete beam. The experimental results demonstrated that the stirrups are very effective in providing the interaction between the two components of the beams. The degree of shear connection emerged not to have effect on the behaviour of tested beams. Three-dimensional finite element analysis was conducted using commercial software ABAQUS. To model the shear connection in composite reinforced concrete beam, the stirrups were connected to the web of the steel T-section by springs at the location of the stirrups. Good agreement is obtained between the results of the experimental tests and the finite element analysis.